2008
DOI: 10.1002/humu.20629
|View full text |Cite
|
Sign up to set email alerts
|

CoagMDB: a database analysis of missense mutations within four conserved domains in five vitamin K-dependent coagulation serine proteases using a text-mining tool

Abstract: Communicated by John McVeyCentral repositories of mutations that combine structural, sequence, and phenotypic information in related proteins will facilitate the diagnosis and molecular understanding of diseases associated with them. Coagulation involves the sequential activation of serine proteases and regulators in order to yield stable blood clots while maintaining hemostasis. Five coagulation serine proteases-factor VII (F7), factor IX (F9), factor X (F10), protein C (PROC), and thrombin (F2)-exhibit high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In vivo and in vitro studies on the function of nsSNPs have found that genetic mutations in F8 and F9 gene are responsible for Haemohpilia A and Haemohpilia B. There have been a quite lot of studies existing to validate the importance of single amino acid substitutions in Haemophlia A and Haemophilia B at activation cleavage sites [65,133,134], affecting factor VIII binding to von Willebrand factor [65,101,135] factor VIII secretion [92] and factor IX binding to factor VIII [136-138]. Recently Markoff by his homology modeling approach analyzed the impact of substitutions in loss of S-S bridges, thrombin activation site, gain/loss of H-bonds, cross-chain H-bonds, ionic bond and possible contact residue in FVIII [132].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo and in vitro studies on the function of nsSNPs have found that genetic mutations in F8 and F9 gene are responsible for Haemohpilia A and Haemohpilia B. There have been a quite lot of studies existing to validate the importance of single amino acid substitutions in Haemophlia A and Haemophilia B at activation cleavage sites [65,133,134], affecting factor VIII binding to von Willebrand factor [65,101,135] factor VIII secretion [92] and factor IX binding to factor VIII [136-138]. Recently Markoff by his homology modeling approach analyzed the impact of substitutions in loss of S-S bridges, thrombin activation site, gain/loss of H-bonds, cross-chain H-bonds, ionic bond and possible contact residue in FVIII [132].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Markoff by his homology modeling approach analyzed the impact of substitutions in loss of S-S bridges, thrombin activation site, gain/loss of H-bonds, cross-chain H-bonds, ionic bond and possible contact residue in FVIII [132]. The information regarding the involvement of mutations in Gla (g-carboxyglutamic acid) domain, EGF1 for the N-terminal domain that binds calcium, EGF2 where it does not bind calcium, and a catalytic serine protease (SP) domain has been deposited in CoagMDB database [138]. The most commonly observed amino acid substitutions are Arg, Tyr, Phe and Cys in FVIII and FIX which play important role in altering the protein function.…”
Section: Discussionmentioning
confidence: 99%
“…Infants with severe deficiency present with massive thrombotic complications, and if they survive due to maintenance replacement therapy, they tend to present with mental retardation and/or visual impairment [82, 83]. Hundreds of mutations of protein C in thrombosis patients have been reported (see protein C mutation databases [84, 85]) and the basis for hereditary protein C defects can most often be rationalized based on the structure of protein C [86, 87]. Acquired protein C deficiency arises during initiation of Coumadin therapy due to the relatively short half life of protein C (T ½ ~ 8 h) compared to most procoagulant vitamin K-dependent factors (T ½ ~ 20 to 48 h), leading to the conventional wisdom of using heparin during initiation of therapy.…”
Section: Protein C Anticoagulant Pathway and Venous Thrombosismentioning
confidence: 99%
“…Biomedical text mining is a large field with a wide range of applications such as the automatized extraction of protein–protein interactions [Krallinger et al, 2011], protein mutations [Caporaso et al, 2007; Doughty et al, 2011; Lee et al, 2007; Rebholz‐Schuhmann et al, 2004], pharmacokinetic relationships between genes, drugs, and diseases [Frijters et al, 2010; Garten et al, 2010; Rubin et al, 2005] or protein and gene annotation [Camon et al, 2005]. Several methods have been implemented and applied successfully to mine human kinase mutations [Krallinger et al, 2009], mutations of G‐protein coupled receptors (GPCRs), nuclear hormone receptors (NRs) [Horn et al, 2004], vitamin K‐dependent coagulation serine proteases [Saunders and Perkins, 2008], and α‐galactosidase A mutations related to Fabry disease [Kuipers et al, 2010]. A database that aims to gather protein level enzyme mutations having an effect on protein stability or function from PubMed abstracts is also available [Yeniterzi and Sezerman, 2009].…”
Section: Introductionmentioning
confidence: 99%